2015
DOI: 10.1177/0022042615580990
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Pattern of Domestic Cannabis Cultivation in the United Kingdom and Its Impact on the Cannabis Market

Abstract: With improvements in both technology and information cannabis is being increasingly grown indoors for domestic use, rather than being imported. This study examines 50 cannabis farms detected by an English police force, and examines the characteristics of the 61 suspects associated with them. The study highlights a UK pattern in domestic cultivation, that is moving away from large scale commercial cultivation, at times co-ordinated by South East Asian organised crime groups, to increased cultivation within resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
(31 reference statements)
0
4
1
Order By: Relevance
“…Whilst UK research has found evidence of links between cannabis production and OCGs, this was demonstrably in a small minority of cases (Kirby and Penna, 2010;Kirby and Peal, 2015). In the current research, assumptions of violent, large-scale and/or OCG-linked cultivators were contradicted by reporting from professionals and cultivators themselves, of a profile of oftenvulnerable individuals cultivating due to debt (not only drug specific debt but general domestic debt in the current economy).…”
Section: Criminals and Criminalisationcontrasting
confidence: 52%
See 1 more Smart Citation
“…Whilst UK research has found evidence of links between cannabis production and OCGs, this was demonstrably in a small minority of cases (Kirby and Penna, 2010;Kirby and Peal, 2015). In the current research, assumptions of violent, large-scale and/or OCG-linked cultivators were contradicted by reporting from professionals and cultivators themselves, of a profile of oftenvulnerable individuals cultivating due to debt (not only drug specific debt but general domestic debt in the current economy).…”
Section: Criminals and Criminalisationcontrasting
confidence: 52%
“…This reflects a common global change to self-sufficient cannabis production, particularly across developed nations (Decorte and Potter, 2015). Secondly, there has been a shift in the type of cultivation, from large-scale commercial production in industrial property to a 'franchising' model using smaller residential or domestic premises (Kirby and Peal, 2015) in order to reduce both legal (detection and prosecution) risks and the potential for illegal 'taxing' (theft) of crops. Notably, the latter is increasingly reported as a means by which local individuals can be controlled through debt bondage by the dealers for whom they produce the crop (ACPO, 2012), to the extent that the phenomenon is being described by Police Chiefs as 'modern slavery' (NPCC, 2014) with specific association with organised criminal gangs (Silverstone, 2011).…”
Section: Introduction: the Cannabis Cultivation Terrainmentioning
confidence: 99%
“…International studies have shown a connection between the size of the plantation and the level of criminal behaviour of those involved in cultivation. As more cultivation has moved to family settings, less involvement of criminal hierarchies have been noticed (Hakkarainen & Perälä 2011;Wiecko & Thompson 2014;Potter & Klein 2020;Kirby & Peal 2015). However, in the literature, there is a division between cultivation for non-profit purposes and profit purposes.…”
Section: C) Criminal Records Of the Accusedmentioning
confidence: 99%
“…Most of the cannabis growers that are prosecuted by the police are men. While men represent 95% of the total accused under the selected sample, men and boys represent more than 98% of the total accused for drug-related crimes for the selected years at country level following the general trend of those involved in cannabis cultivation (Alvarez, Gamella & Parra 2016;Hakkarainen & Perälä 2011;Kirby & Peal 2015). The percentage of women involved does not fluctuate throughout the years (author's calculations from the General Prosecutor Office reports 2014-2020).…”
mentioning
confidence: 99%
“…Canada, Mexico and the US are now among the major cannabis producers in America, and Australia and New Zealand are described as close to self-sufficiency (UNODC, 2015). In Europe, countries such as the Netherlands, Belgium, Italy and the United Kingdom -formerly importers of cannabis resin -have developed their own marihuana-producing industries (Decorte, Potter, & Bouchard, 2011;Decorte, 2007Decorte, , 2010EMCDDA, 2012;Jansen, 2002;Kirby & Peal, 2015;Korf, 2011;Potter, 2008Potter, , 2010UNODC, 2015;Wouters, 2008).…”
Section: Introductionmentioning
confidence: 99%